2022
DOI: 10.1038/s41598-022-08867-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potentially functional circular RNAs hsa_circ_0070934 and hsa_circ_0004315 as prognostic factors of hepatocellular carcinoma by integrated bioinformatics analysis

Abstract: Hepatocellular carcinoma (HCC) is one of the most prevalent cancers worldwide, which has a high mortality rate and poor treatment outcomes with yet unknown molecular basis. It seems that gene expression plays a pivotal role in the pathogenesis of the disease. Circular RNAs (circRNAs) can interact with microRNAs (miRNAs) to regulate gene expression in various malignancies by acting as competitive endogenous RNAs (ceRNAs). However, the potential pathogenesis roles of the ceRNA network among circRNA/miRNA/mRNA in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…Similarly, in another bioinformatics study, CDC6 is the core gene of HCC and is associated with tumor regulatory pathways. [ 34 , 35 ] The above literature review is consistent with our results, our study found that the high expression of CDC6 in HCC, the higher the CDC6, the worse the prognosis. Therefore, it is speculated that CDC6 may play an important role in the occurrence and development of liver cancer, and CDC6 can be used as a potential target for HCC therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in another bioinformatics study, CDC6 is the core gene of HCC and is associated with tumor regulatory pathways. [ 34 , 35 ] The above literature review is consistent with our results, our study found that the high expression of CDC6 in HCC, the higher the CDC6, the worse the prognosis. Therefore, it is speculated that CDC6 may play an important role in the occurrence and development of liver cancer, and CDC6 can be used as a potential target for HCC therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, our findings were proved again. According to miRTarbase ( Chou et al, 2018 ), miRDB ( Chen and Wang, 2020 ), and Targetscan ( Morovat et al, 2022 ) databases, latent target genes of five miRNAs were forecasted ( Figure 6B ). Unfortunately, hsa-mir-155-5p was not retrieved in the database, and hsa-mir-200b-5p had no overlapped target genes.…”
Section: Resultsmentioning
confidence: 99%
“… 32 LINC00452 and hsa_circ_0070934 are involved in ovarian and hepatocellular carcinoma. 33 , 34 LINC00639, expressed in bronchial epithelial cells, is involved in the development of chronic obstructive pulmonary disease. 35 LINC01783, a rarely studied novel lncRNA, has been found to be highly up-regulated in serum samples.…”
Section: Discussionmentioning
confidence: 99%